Analisis Kesesuaian Lahan Obyek Wisata Pantai Walupiting Kabupaten Batang - Abdillah, Rangga Fajar; Rifandi, Raditya Ahmad (Environmental Science Program, Ivet University, 2023)
Batang Regency, Central Java, has a lot of potential for beach tourism, both those that have been managed and those that have not been managed properly. In determining the beach tourism object according to the designation for tourism, it is necessary to analyze the land suitability of beach tourism objects. Walupiting Beach is one of the tourism potentials owned by Batang Regency which has not been managed. Analysis of land suitability for Walupiting tourism objects was carried out by measuring ten land suitability parameters owned by Walupiting Beach and then adjusted to the designation of coastal tourism. The results of the land suitability analysis obtained a Tourism Land Suitability Index (IKW) value of 91%. The IKW value of 91% indicates that Walupiting Beach is in the very suitable category for land use as a beach tourism. The results of this research are used as suggestions for the government and the surrounding community to determine the management strategy for Walupiting Beach tourism objects. Key Words : Land Suitability, Tourism, Walupiting Beach